Hungarian Monitoring, 5 November 1988 . [Magyar rádiófigyelő], 1988. november 5 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Report from New York on presidential elections - What kind of agreement would the USSR sign with the Common Market? - Follow-up talks in Vienna - Speeches in Moscow at November 7 celebrations - Program of celebrations in USSR for November 7 - Computer virus infections in the US Domestic Affairs: - Károly Grósz's schedule in Vienna - Károly Grósz confirms American companies have been commissioned to assess Hungarian economic property - Pozsgay appointed to oversee keeping relations with national minorities and Hungarians abroad - Károly Grósz rejects re-interpretation of 1956 and announces draft law on regulating emigration - Transylvanian refugees Economy: - Hungarian National Bank issues bonds in Switzerland worth CHF 75 million - Interview with deputy president of Chamber of Commerce on Hungarian economic and technology days in Portugal and economic relations between the two countries Külpolitika: - New York-i tudósítás az elnökválasztás esélyeiről - Milyen szerződéseket szeretne kötni a SZU a közös piaccal? - A bécsi utótalálkozóról - Ünnepi beszéd Moszkvában a november 7-i ünnepségen - Ünnepi programok a SZU-ban az novemberi ünnepségekre - Computer-vírus fertőz az Egyesült Államokban Belpolitika: - Grósz Károly bécsi programja - Grósz közölte, amerikai céget bíztak meg a magyar gazdasági vagyon felmérésére - A nemzetiségekkel és a külföldi magyarokkal való kapcsolat tartására Pozsgay kapott megbízást - Grósz elutasította az 56-os események újraértékelését és közölte, törvényjavaslat készül a kivándorlás szabályozására - Az erdélyi menekültek helyzete Gazdaság: - 75 millió svájci frank értékben a Magyar Nemzeti Bank Svájcban bocsátott ki kötvényt - Interjú a Gazdasági Kamara alelnökével a Portugáliában rendezett magyar gazdasági és műszaki napok kapcsán a két ország gazdasági kapcsolatairól